Korelasi Ilmu Pengetahuan dan Teknologi Dengan Al-Qur’an - Abnisa, Almaydza Pratama; Muin, M. Tamsil (STAI Asy-Syukriyyah, 2024)
Understanding the relationship between the Qur'an and science, not by looking at whether there are scientific theories or new discoveries contained in it, but by seeing whether the Qur'an or the spirit of its verses hinders the progress of science, and even the Koran encourages the progress of science. In the perspective of the Al-Qur'an, scientific signals and suggestions from the Al-Qur'an to humans to use their minds are the basis of science which must be considered, thought about, pondered, researched and developed for the sake of the greatness and welfare of mankind. The Qur'an as a source of knowledge provides the most essential basic seeds so that humans can develop into science and technology that is unlimited in variety and has unlimited directions for achievement. Apart from that, the Qur'an will guarantee the truth of the knowledge that comes from it, the truth of the direction of its development, because everything comes from the Sunnah of Allah, and the spirit of devotion and faith of humans as subjects who adhere to this understanding. carry it out. The limits of human authority to acquire knowledge have also been established in the Al-Qur'an.